Review of the book Why are there no political parties in Peru? - Evans Morales, Franco (2020)
The present review aims to present and discuss the reasons that lead politicians to use personalistic vehicles to compete in national and subnational elections away from political party membership. Starting in the nineties, with the collapse and crisis of the political party system in Peru, lonely politicians understand that to win elections and gain access to representative power, they have to serve as partisan substitutes or surrogates to guarantee incentives, resources and political trajectories in the short term.